PENYELENGGARAAN PROGRAM PAUD (STUDI EVALUATIF DI POS PAUD KOTA JAKARTA TIMUR, PROVINSI DKI JAKARTA) - Hartati, Sofia (JIV-Jurnal Ilmiah Visi, 2017)
Cases of sexual violence in children are very apprehensive so that they make parents become more alert and frightened about their children safety. This research discusses how important communication between parents and children is, particularly the stage of early childhood, to give them understanding of self-protection. Communication has to be built from early childhood due to the fact that there will be a good relationship between parents and children. For families who have problems with unnatural characteristics and children who need to be taken care, then their family problems are the first things to overcome. A child who does not have a father or mother becomes a priority to be paid more attention by government. For families who have abilities in taking care children well and having sufficient knowledge to teach and protect them from violence and harassment, then communication between parents and children is necessary, through sex education for them, honest disclosure, harmonic interpersonal communication, the use of good language, and motivation to be independent. Barriers in communication in a family can be overcome by providing time to communicate, creating an attitude of openness, mutual respect, appreciation, and supportive attitude toward children.